Migration Competition in Enlarged European Union: A Theoretical Model - Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
In this article, we propose a theoretical model which help us to define two possible settings where the European "migration competition" could be analysed. First, we analyse the scenario in which there are two regions: a receiving country and a net sending country. In this scenario we introduce the possibility for each country to increase, by investing resources, the level of integration between countries which consequently reduces the level of migration costs. Thus it is possible to capture the receiving country's trade off between investing resources in order to attract foreign high skilled workers or investing on educational incentives for his citizens. Second, we analyse the scenario in which there are three regions. Starting from the first scenario's framework, we could analyse either the case in which a new country is able to intercept a significant quota of the flow of skilled migrants, either the effect of migration competition between the two regions in order to attract the skilled workers of the sending country. In both case analysed, the presence of a central authority which coordinates the migration and fiscal policies is determinant to obtain better results.
Keywords: 330